Perspectives on the Legal Guardianship of Children in Côte d'Ivoire, South Africa, and Uganda - Sarumi, Rofiah Ololade (SpringerBriefs in Social Work,, 2018)
This brief reference surveys the national policy of three representative African countries on the legal guardianship of children who are without parents or families. Focusing on the widely varying legal systems of Côte d'Ivoire, South Africa, and Uganda, the authors highlight guardianship as emblematic of the continent's shortcomings in child protection laws. The book's key objective is bridging the communal aspects of traditional African society with the global standards set forth by the Convention on the Rights of the Child and other international entities. To this end, the three frameworks discussed here are compared and their strengths and limitations evaluated as applied to child protection standards in terms of core guardianship issues: Holders of parental authority and responsibilities Appointment of a legal guardian Who qualifies as a legal guardian? Responsibilities of a legal guardian in relation to the child Termination of guardianships The primary audience for Perspectives on the Legal Guardianship of Children in Côte d'Ivoire, South Africa, and Uganda includes academics, researchers, and students in the fields of children's rights, human rights, legal guardianship, and international law. It will also prove a useful reference for NGOs that focus on children's rights, social workers and practitioners operating within the context of these three countries, professionals working within the African human rights system, and governmental law- and policymakers.